Refocusing Neuroprotection in Cerebral Reperfusion Era: New Challenges and Strategies - Xiong, Xiao-Yi; Liu, Liang; Yang, Qing-Wu (Frontiers in Neurology, 2018)
Pathophysiological processes of stroke have revealed that the damaged brain should be considered as an integral structure to be protected. However, promising neuroprotective drugs have failed when translated to clinical trials. In this review, we evaluated previous studies of neuroprotection and found that unsound patient selection and evaluation methods, single-target treatments, etc., without cerebral revascularization may be major reasons of failed neuroprotective strategies. Fortunately, this may be reversed by recent advances that provide increased revascularization with increased availability of endovascular procedures. However, the current improved effects of endovascular therapy are not able to match to the higher rate of revascularization, which may be ascribed to cerebral ischemia/reperfusion injury and lacking of neuroprotection. Accordingly, we suggest various research strategies to improve the lower therapeutic efficacy for ischemic stroke treatment: (1) multi-target neuroprotectant combinative therapy (cocktail therapy) should be investigated and performed based on revascularization; (2) and more efforts should be dedicated to shifting research emphasis to establish recirculation, increasing functional collateral circulation and elucidating brain-blood barrier damage mechanisms to reduce hemorrhagic transformation. Therefore, we propose that a comprehensive neuroprotective strategy before and after the endovascular treatment may speed progress toward improving neuroprotection after stroke to protect against brain injury.